The Problem of the Media : U.S. Communication Politics in the Twenty-First Century - McChesney, Robert Waterman, 1952- (Book collections on Project MUSE., 2004)
Examines the media system in the U.S., discussing corporate control and hyper-commercialism, and argues that informed public participation in media policy making is needed to ensure the health of American democracy and culture.